Correction: Opening the Black Box of Scholarly Communication Funding: A Public Data Infrastructure for Financial Flows in Academic Publishing. Issue 1 (28th April 2016) - Lawson, Stuart; Gray, Jonathan; Mauri, Michele
This article details a correction to article Lawson, S, Gray, J and Mauri, M 2016 Opening the Black Box of Scholarly Communication Funding: A Public Data Infrastructure for Financial Flows in Academic Publishing. Open Library of Humanities, 2(1): e10, pp. 1–35, DOI:http://dx.doi.org/10.16995/olh.72